2010
DOI: 10.1186/1479-5868-7-5
|View full text |Cite
|
Sign up to set email alerts
|

Advocacy for active transport: advocate and city council perspectives

Abstract: BackgroundEffective advocacy is an important part of efforts to increase population participation in physical activity. Research about effective health advocacy is scarce, however, the health sector can learn from the experiences and knowledge of community advocates and those who are on the receiving end of this advocacy. The aim of this study is to explore advocacy for active transport from the perspectives of community advocates and representatives from City councils.MethodsCycling and walking advocates were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 13 publications
1
21
0
Order By: Relevance
“…These included concerns about injury risk, obesity, physical inactivity, personal safety and facilities for people with disabilities. Previous research has identified a tendency for emphasis of injury risk over health benefits [ 16 , 30 ] and this was also true in the total sample in the current study. While not disputing the importance of reducing injury risk, it would appear that there is a need for greater emphasis of the health benefits of active transport.…”
Section: Discussionsupporting
confidence: 60%
See 4 more Smart Citations
“…These included concerns about injury risk, obesity, physical inactivity, personal safety and facilities for people with disabilities. Previous research has identified a tendency for emphasis of injury risk over health benefits [ 16 , 30 ] and this was also true in the total sample in the current study. While not disputing the importance of reducing injury risk, it would appear that there is a need for greater emphasis of the health benefits of active transport.…”
Section: Discussionsupporting
confidence: 60%
“…Identification and understanding of opposition arguments is an important part of advocacy efforts, firstly to guide attempts to find win-win scenarios where the wishes of both parties are met, or alternatively to allow counterarguments to be developed to limit the impact of entrenched opposition [36]. Similar to previous studies, the cost or resources needed to carry out active transport initiatives was a concern [10,16]. In New Zealand, homeowners pay an annual fee to the local council to help pay for local services.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations